Experiences of recent veterinary graduates in their first employment position and their preferences for new graduate support programmes. Issue 4 (3rd July 2020) - Gates, MC; McLachlan, I; Butler, S; Weston, JF
ABSTRACT: Aims: To explore the experiences of recent veterinary graduates in their first employment position, to investigate risk factors for leaving this position, and to identify their preferences towards new graduate support programmes. Methods: All 693 individuals who completed their veterinary degree and registered with the Veterinary Council of New Zealand between May 2014 and May 2019 were invited to participate in a cross-sectional survey regarding their employment experiences. Descriptive statistics were calculated for all study variables and a multivariable logistic regression model was constructed to explore factors associated with increased risk of new graduates leaving their first position. Thematic analysis was performed on the free-text comments to identify key issues with new graduate support. Results: The survey was completed by 162/693 veterinarians (23.4%). Of 153 respondents who provided information on their first employment position, 61 (39.9%) commenced their veterinary career in companion animal practice, 44 (28.8%) in mixed animal practice, 36 (23.5%) in large animal practice, and 12 (7.8%) worked in another veterinary discipline. Most respondents (124/153; 81.0%) were rostered for after-hours emergency shifts during their first year with variable levels of support from their practice. Among 72 respondents (44.4%) who had left their first job, the mean length of employment was 1.4 (median 1; min 1; max 4) years. The most common reasons reported for leaving were a toxic practice culture and lack of adequate support. The risk of leaving was increased by being put in situations they could not handle (OR 5.26; 95% CI = 1.49–20.6) and employers that did not regularly check their wellbeing (OR 5.08; 95% CI = 1.52–18.9). Only 56/144 (38.9%) respondents and 30/144 (20.8%) respondents supported introducing compulsory checklists of technical and soft skills, respectively. Providing regular feedback, creating a supportive practice culture, setting reasonable workload expectations, providing clinical and professional advice, and developing tailored skills development plans were identified as key areas that employers of new graduates should address. Conclusions: Lack of appropriate mentoring and toxic practice cultures were the most common reasons for new graduates leaving their first job. Although respondents identified that employers should provide new graduates with better support, most were not supportive of introducing a compulsory programme. Clinical relevance: To help new graduates transition into their first professional veterinary roles, employers should ensure that new graduates are only placed in situations that they can handle competently and check regularly on their mental and physical wellbeing.